The Effect Of Slow Deep Breathing Therapy On Reducing Post Sectio Patient Intensity Caesarea In General Hospital Mom Kartini Kisaran Year 2023 - Syamsul Idris (Sean Institute, 2023)
Surgery or operations are all invasive actions by opening or displaying the body part to be treated. One of the most common cases of surgery performed in the world is sectio caesarea. Sectio caesarea surgery procedures can cause incisions. The incisions made can cause various complaints, one of the most common felt by patients is pain. The purpose of this study was to determine the effect of slow deep breathing therapy on reducing pain intensity in post sectio caesarea patients at Ibu Kartini Kisaran General Hospital in 2023. This study used a Pre-Experimental Design with a one-group pretest-posttest design approach. This study was conducted from March 20 2023 to March 31 2023. The population in this study were all post sectio caesarea patients from January 2023 to February 2023 as many as 49 people. The sampling technique used the accidental sampling technique with a total of 16 people. The results of the study found that the pain intensity of post-cesarean section patients before the implementation of slow deep breathing therapy at Ibu Kartini Kisaran General Hospital in 2023 as a whole was moderate pain and the pain intensity of post-section caesarea patients after the implementation of slow deep breathing therapy at Ibu Kartini Kisaran General Hospital In 2023, even though the majority still feel mild pain, after doing slow deep breathing therapy, there are some who experience mild pain. Based on the results of the paired t-test, the value of p = 0.001 <a = 0.05 was obtained The conclusion in this study is that there is an effect of slow deep breathing therapy on reducing the pain intensity of post sectio caesarea patients at the Ibu Kartini Kisaran General Hospital in 2023. The suggestion in the research is that with the research of the Ibu Kartini Kisaran General Hospital, it should combine drug administration and implementation of slow therapy. deep breathing to reduce pain intensity in pain patients.